On a class of controls of the Poisson process - Grigelionis, B. (Lithuanian Mathematical Journal, 1965)
The abstracts (in two languages) can be found in the pdf file of the article.Original author name(s) and title in Russian and Lithuanian:Б. Григелионис. Об одном классе управлений пуассоновским процессомB. Grigelionis. Apie vieną Puasono proceso valdymų klasę